Comparative Study of Conventional and Spatial Panel Models in Analyzing the Information and Communication Technology Development Index - Saifudin, Toha; Marthabakti, Citrawani; Wieldyanisa, Ezha Easyfa (Statistics, Optimization & Information Computing, 2026)
Indonesia continues to face digital inequality, both in terms of inter-provincial disparities and in comparison, to other countries in Southeast Asia, where it lags behind Vietnam and is far below Singapore. These disparities highlight spatial heterogeneity, where regional characteristics influence by Information and Communication Technology (ICT) capacity differently, and spatial dependence, where development in one province can spill over to others. Given the strategic importance of ICT in driving sustainable growth, overcoming such inequality is crucial. This challenge is also strongly linked to SDG 9 and SDG 10, which emphasize inclusive digital development as a pathway to reducing gaps across regions. This research seeks to examine the determinants affecting Information and Communication Technology Development Index (ICT-DI) across Indonesian province by contrasting traditional panel data models with spatial panel modeling techniques. Secondary data from Central Bureau of Statistics (Indonesia) for 2020-2023 were used. Descriptive analysis and thematic mapping were conducted, followed by estimation using the panel model, as well as spatial panel models including Spatial Autoregressive Fixed Effect (SAR-FE) and Spatial Error Model Fixed Effect (SEM-FE). The results indicate significant spatial dependence across provinces, confirming the relevance of spatial analysis. The SAR-FE model was identified as the best model, explaining 98.47% of the variation in ICT-DI with the lowest MAPE value (1.1023). Population density was identified as the only significant positive factor, indicating that more densely populated regions tend to have better ICT infrastructure and capacity. The findings emphasize the novelty of applying spatial panel models to ICT analysis in Indonesia and underline their policy relevance. Considering dependence and heterogeneity enables policymakers to design more inclusive and sustainable strategies, tailored to the unique priorities of each province, to reduce digital inequality.